Provocative engagement: Documentary audiences and performances in The Act of Killing and The Look of Silence. (September 2019) - Hill, Annette; Askanius, Tina; Kondo, Koko; Luis Urueta, Jose
Through an analysis of The Act of Killing (2012) and The Look of Silence (2014), this article explores the idea of provocative engagement as a way of extending our understanding of the affective dimensions of documentary and its role in civic engagement. The study draws on qualitative research, based on interviews with the filmmaker, and interviews with 52 viewers in Denmark, Sweden, Japan and Colombia. This data is used to explore the idea of subjectivity in documentary through the performance of memory, power and impunity in both films concerning the perpetrators and victims of the Indonesian genocide of 1965. Overall, our analysis highlights how performance documentary challenges the affective relationships between filmmakers and their audiences, and in this particular case we see a type of raw, provocative engagement with the act of documenting genocide, the act of watching, and what this means to people in the context of their political and lived realities.